Development of Maize Seed Production Technology - CGIAR Research Program on Maize (2020)
It is a Stage 1, this methodology were has been tested under field controlled conditions. It is necessary to evaluate germplasm of relevance in the specific geographies and relevant production periods where inbred lines management and commercial seed production of hybrids is desired.